2023
DOI: 10.1037/rep0000487
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy trajectories of individuals newly diagnosed with multiple sclerosis.

Abstract: Purpose/Objective: The first year following a new multiple sclerosis (MS) diagnosis may be a critical time for individuals as they learn to manage their disease. Effective self-management of MS likely requires healthy self-efficacy levels, yet little is known about self-efficacy in the postdiagnosis period. This study aims to improve our understanding of self-efficacy in individuals newly diagnosed with MS by examining self-efficacy trajectories and identifying patient characteristics associated with trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…27 Research by Karademas et al 24 showed that promoting coping selfefficacy should be considered as an intervention-oriented goal for breast cancer patients to improve their well-being. Research has also shown that intolerance of uncertainty 28 and cognitive fusion 29 predicts coping self-efficacy pathways in people with chronic physical EYNI and MOUSAVI illnesses. Research by Onyedibe et al 30 showed that cancer selfefficacy plays a mediating role in the relationship between mental adaptation to cancer and health-related quality of life in cancer patients.…”
mentioning
confidence: 99%
“…27 Research by Karademas et al 24 showed that promoting coping selfefficacy should be considered as an intervention-oriented goal for breast cancer patients to improve their well-being. Research has also shown that intolerance of uncertainty 28 and cognitive fusion 29 predicts coping self-efficacy pathways in people with chronic physical EYNI and MOUSAVI illnesses. Research by Onyedibe et al 30 showed that cancer selfefficacy plays a mediating role in the relationship between mental adaptation to cancer and health-related quality of life in cancer patients.…”
mentioning
confidence: 99%